أثر برنامج نفس حركي في تنمية إلانتباه إلانتقائي لدى أطفال متلازمة داون القابلون للتعلم - بوعنان,عاشورة; حمادن,وفاء (University of Eloued جامعة الوادي, 2024)
This study aimed to develop selective attention among children with down syndrome who are capable of learning ysing a bsychomotor program. This study was comducted on a sample consisting of 5 children who were intentionally selected, studying at the psychopedagogical center for mentally disabled childen in chott oued. The Stroop test and observation were used in our study. In the training program, we followed the experimental approach, used the SPSS system, used the arithmetic mean, standard deviation, and the T test, and we areached the following result: the psychomotor program in developing selective attentiom in children with down syndrome has a significant impact. هدفت هذه الدراسة إلى تنمية الانتباه الانتقائي لدى أطفال متلازمة داون القابلون للتعلم باستخدام برنامج نفس حركي، حيث تم اجراء هذه الدراسة على عينة تكونت من 5 أطفال تم اختيارهم بطريقة قصدية، يتمدرسون بالمركز النفسي البيداغوحي للأطفال المعاقين ذهنيا بالشط الوادي، وتم استخدام في دراستنا هذه اختبار ستروب والملاحظة والبرنامج التدريبي حيث اتبعنا المنهج التجريبي، واستخدمنا نظام Spss واستخدمنا المتوسط الحسابي والانحراف المعياري واختبار T test وتوصلنا إلى النتيجة التالية: أن البرنامج النفس الحركي في تنمية الانتباه الانتقائي لدى أطفال متلازمة داون له اثر كبير
Keywords: Breathwork program; Down's syndrome; selective attention; برنامج نفس حركي; متلازمة داون; الإنتباه الإنتقائي